2003
DOI: 10.1046/j.1364-3703.2003.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

The Fusarium graminearum MAP1 gene is essential for pathogenicity and development of perithecia

Abstract: SUMMARY Fusarium graminearum is the causal agent of ear blight disease of cereals. Infection occurs at anthesis when ascospores and/or conidia directly penetrate exposed anther and ovary tissue. The hemibiotrophic hyphae colonize floral tissues and developing grains to cause premature ear senescence. During infection, Fusarium hyphae can also produce hazardous trichothecene mycotoxins, thereby posing a threat to human and animal health and safety. The Fusarium MAP1 gene was identified using a PCR approach by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(136 citation statements)
references
References 60 publications
3
130
1
Order By: Relevance
“…In B. cinerea, inactivation of the MAPK gene BMP1 (here renamed Bci-Kss1) results in strains that are essentially nonpathogenic, since infection hyphae fail to penetrate and macerate plant tissues (Zheng et al, 2000;Doehlemann et al, 2006). Independent studies also revealed that deletion of the MAPK gene MAP1/Gpmk1 (here renamed Fgr-Kss1) hinders pathogenicity of Fusarium graminearum, the causal agent of wheat head-blight disease (Jenczmionka et al, 2003;Urban et al, 2003). Again, apathogenicity of Fgr-kss1 mutants could be associated with diminished or delayed induction of enzymatic activity normally associated with degradation of the plant cell wall (Jenczmionka and Schäfer, 2005).…”
Section: Kss1/fus3-type Mapks In Other Phytopathogenic Fungimentioning
confidence: 99%
“…In B. cinerea, inactivation of the MAPK gene BMP1 (here renamed Bci-Kss1) results in strains that are essentially nonpathogenic, since infection hyphae fail to penetrate and macerate plant tissues (Zheng et al, 2000;Doehlemann et al, 2006). Independent studies also revealed that deletion of the MAPK gene MAP1/Gpmk1 (here renamed Fgr-Kss1) hinders pathogenicity of Fusarium graminearum, the causal agent of wheat head-blight disease (Jenczmionka et al, 2003;Urban et al, 2003). Again, apathogenicity of Fgr-kss1 mutants could be associated with diminished or delayed induction of enzymatic activity normally associated with degradation of the plant cell wall (Jenczmionka and Schäfer, 2005).…”
Section: Kss1/fus3-type Mapks In Other Phytopathogenic Fungimentioning
confidence: 99%
“…22 The Fus3 homolog also plays a critical role in virulence of other phytopathogenic fungi, including A. brassicicola, Bipolaris oryzae, Botrytis cinerea, Claviceps purpurea, C. heterostrophus, Colletotrichum lagenarium, Cryphonectria parasitica, Fusarium spp., Mycosphaerella graminicola, Pyrenophora teres, Stagonospora nodorum and Verticillium dahliae. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The Fus3 homolog (Cek1) is also an important virulence determinant in the opportunistic human pathogen Candida albicans. 38 The AaFus3 gene encoding a homolog of the yeast Fus3-like MAP kinase was cloned and 39 In addition, the Fus3 MAPK-mediated signaling pathway is involved in conidia formation and maturation in A. alternata, since Dfus3 mutant does not produce any conidia.…”
Section: Introductionmentioning
confidence: 99%
“…Mutants for eight such genes have been characterized using various techniques. The genes identified and verified by gene disruption or replacement include the Tri5 gene of the trichothecene gene cluster encoding trichodiene synthase (Proctor et al, 1995), two MAP kinase genes, Mgv1 (Hou et al, 2002) and Map1, also called gpmk1 (Jenczmionka et al, 2003;Urban et al, 2003), a secreted lipase gene, Fgl1 (Voigt et al, 2005), a gene similar to Cps1 from Cochliobolus heterostrophus (Lu et al, 2003) and two polyketide synthase genes, Zea1 (PKS4) and Zea2 (PKS13), involved in the synthesis of the mycotoxin zearalenone (Gaffoor et al, 2005;Kim et al, 2005). Apart from these, genes encoding a predicted NADH : ubiquinone oxidoreductase, a putative b-ZIP transcription factor, a transducin b-subunit-like protein, as well as hydroxymethylglutaryl-CoA reductase (HMR1) and cystathionine beta-lyase (CBL1) have also been identified to be involved in pathogenicity through restriction-enzyme-mediated insertion (REMI) and directed mutagenesis (Seong et al, 2005(Seong et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%